2015
DOI: 10.1186/s12906-015-0581-z
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological studies of stem bark extract from Schefflera barteri Harms (Araliaceae)

Abstract: BackgroundThe use of herbal medicines as complements or alternatives to orthodox medicines has been on the increase. There has been the erroneous belief that these medicines are free from adverse effects. Schefflera barteri is popularly used in the West region of Cameroon for the treatment of various diseases such as diarrhea, spasm, pneumonia and animals bite. Considering the ethnopharmacological relevance of this plant, this study was designed to investigate the possible toxic effects of the stem bark extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
5
7
0
Order By: Relevance
“…Its level is increased in the serum when the cortex and/or the glomeruli are damaged. Thus, higher than normal levels of serum creatinine are an indication of a deficiency in renal function [16,22]. In the current study, serum creatinine level significantly increased in the male mice treated with the extract at the highest dose of 800 mg/kg.…”
Section: Test Groups Satellite Groupssupporting
confidence: 51%
See 1 more Smart Citation
“…Its level is increased in the serum when the cortex and/or the glomeruli are damaged. Thus, higher than normal levels of serum creatinine are an indication of a deficiency in renal function [16,22]. In the current study, serum creatinine level significantly increased in the male mice treated with the extract at the highest dose of 800 mg/kg.…”
Section: Test Groups Satellite Groupssupporting
confidence: 51%
“…The hematopoietic system is one of the most sensitive targets for toxic compounds and an important index of physiological and pathological status in man and animal [21]. In this study, an oral administration of CuAE to male and female mice for 28 consecutive days did not affect neither RBCs count nor HGB, nor HCT, suggesting that this extract has no oxygenation and anemia risk [22]. Total WBCs and differential leukocytes of mice of both sexes of the test groups and the test satellite group showed no significant difference with control groups.…”
Section: Test Groups Satellite Groupsmentioning
confidence: 50%
“…The results obtained from the present study showed that LSE did not cause rat mortality or other signs of toxicity even at a dose limit of 5000mg /kgbw. This result is in agreement with the reports of Kabiru et al [14], and Atsafack et al [15], that revealed that methanolic leaf extract of Eucalyptus camaldulensis exhibited LD 50 above 5000mg/kgbw and was, therefore, considered non-toxic acutely.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, the creatinine levels were significantly lower in the SMBT‐treated animals (Table ). Creatinine is a marker of kidney toxicity, its levels increased in the serum when the cortex and/or the glomerular kidney structures are damaged (Atsafack et al, ). In this case, the decreased levels of serum creatinine in SMBT‐treated mice may suggest malnutrition and/or loss of body mass, conditions that in this study were discarded because differences in the weight of the body and organs were not found (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…During the treatment period, animals were observed on general signs of toxicity, behavior, and mortality. Body weights were measured on days 1, 7, 17, 24, and 30 (Atsafack et al, ). At the end of the experiment (day 30), animals were anesthetized with ketamine/xylasin (100/20 mg/kg i.p.…”
Section: Methodsmentioning
confidence: 99%